2018
DOI: 10.3892/mmr.2018.9033
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells and endothelin‑1 promote the odontogenic differentiation of dental pulp stem cells

Abstract: It has been established that dental pulp stem cells (DPSCs) serve an important role in the restoration and regeneration of dental tissues. DPSCs are present in blood vessels and also exist in the vessel microenvironment in vivo and have a close association with endothelial cells (ECs). The present study aimed to evaluate the influence of ECs and their secretory product endothelin-1 (ET-1) on the differentiation of DPSCs. In the present study, cells were divided into four groups: i) a DPSC-only control group; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…This was also supported by previous reports, which suggested that ultradian locomotor activity oscillations persisted in rodents housed in DD, even upon ablation of SCN [8] or genetic disruption of the circadian clocks [3]. An 8-hr ultradian rhythm was also observed in circulating endothelin-1 (ET-1) in human blood [6], and a study using dental pulp stem cells suggested that ET-1 promotes odontogenic differentiation [12], suggesting that Representative fluorescent microscopic images from mice housed in LD and administrated with tetracycline each week (for 4 weeks) at 1~4 (A) or 5~8 (B) weeks of age. Three fluorescent bands in crown dentin can be observed in panel (A), and no labels can be observed in panel (B), respectively.…”
Section: Discussionsupporting
confidence: 84%
“…This was also supported by previous reports, which suggested that ultradian locomotor activity oscillations persisted in rodents housed in DD, even upon ablation of SCN [8] or genetic disruption of the circadian clocks [3]. An 8-hr ultradian rhythm was also observed in circulating endothelin-1 (ET-1) in human blood [6], and a study using dental pulp stem cells suggested that ET-1 promotes odontogenic differentiation [12], suggesting that Representative fluorescent microscopic images from mice housed in LD and administrated with tetracycline each week (for 4 weeks) at 1~4 (A) or 5~8 (B) weeks of age. Three fluorescent bands in crown dentin can be observed in panel (A), and no labels can be observed in panel (B), respectively.…”
Section: Discussionsupporting
confidence: 84%
“…The application of combined DSCs with the ECM scaffold can be used for root canal therapy. It has been shown that DSCs are able to differentiate into functional odontoblasts with angiogenic potential[ 110 ]. Implantation of a 3D scaffold by shaping sheet-like aggregates of DSCs with a thermos-responsive hydrogel into the human tooth root canal generates pulp-like tissues with rich neovascularization without adding growth factors[ 111 ].…”
Section: Tooth Reconstructionmentioning
confidence: 99%
“…DPSCs exist in the vessel microenvironment in-vivo and have a close association with endothelial cells, which were proved to regulate the development of dentine/pulp tissue [12]. Dissanayaka et al [13] directly co-cultured HUVEC and DPSCs, reporting that endothelial cells may improve the osteo-odontogenic differentiation of DPSCs.…”
Section: Introductionmentioning
confidence: 99%